Developing functional foods from soybean waste via dual fermentation-heat treatment of okara - Tay, Clarisse Siew Cheng (Nanyang Technological University, 2023)
In Asian countries where soymilk consumption is high, a significant amount of okara, a processing side-stream of soybean, is generated. Although it retains various nutrients with high biological value, like dietary fibre and protein, unprocessed okara putrefies easily and has low nutrient bioavailability, causing it to remain under-utilized. The use of probiotic fermentation is often employed to overcome these challenges, however, there are limitations as well as safety concerns of unwanted side effects from the use of live microbes. Hence, this has caused focus to shift towards alternative agents such as postbiotics, also known as non-viable or heat-treated probiotics. Herein, okara was valorised using a dual fermentation-heat treatment method with Lactobacillus sp. and Bifidobacteria sp. to produce postbiotic okara. Compositional analysis revealed a 21% increase in total phenolic content, 156% increase in soluble fibre, and 151% increase in aglycone isoflavones when compared to the unfermented control. However, comparisons of the nutrient composition and metabolic profile between probiotic and postbiotic okara were not significantly different. These results show retention of functionality of probiotic okara post-heat treatment, suggesting that non-viable probiotic foods might be able to exert similar health benefits as that of its viable counterpart. Overall, the improvements achieved in postbiotic okara encourages its use as a functional ingredient that can not only aid in increasing sustainability for the food industry but have an impact on the health and well-being of the population.